Reintegration and Therapeutic Communities in Greece. The Experience and Views of Participants (a case study: Kethea en Drasi) - Aikaterini Ntaflou; Konstantinos Malafantis (Rivista di Criminologia, Vittimologia e Sicurezza)
Substance addiction issues among incarcerated individuals in correctional facilities in Greece and abroad are notably prevalent. Addiction is generally addressed within correctional systems as a pathology with biological, social, psychological, ideological, cultural, economic, and other dimensions. Beyond this, addiction is deeply intertwined with the disciplinary process and the reintegration of prisoners. This involves a range of issues. In particular, it involves not only the cessation of substance use but also the modification of addictive behaviors through education. To achieve this goal, adopting a socially acceptable system of values and life skills through strong and oriented education appears to be crucial. The purpose of this case study (conducted as part of postdoctoral research) was to examine the views of 47 incarcerated individuals who participated in the therapeutic community program of KETHEA en DRASI during the research period regarding therapeutic correctional education programs. The data were analyzed using questionnaires and inductive coding processes to categorize relevant perceptions. According to the study's findings, participation in therapeutic and educational programs simultaneously achieves control and treatment of addictions and educates participants in the cultivation of life skills necessary for their social, educational, and professional reintegration.